79 What we know about acute pediatric cannabis poisoning: A scoping review. (29th October 2021) - Elliott, Sarah; Gaudet, Lindsay; Hogue, Kaitlin; Scott, Shannon; Hartling, Lisa
Abstract: Primary Subject area: Emergency Medicine - Paediatric Background: Liberalization of cannabis policy in Canada has led to concerns that increasing access to cannabis and cannabis infused products (e.g. edibles) for adults will have negative, unintended consequences for children. Objectives: We conducted a scoping review to map the available evidence on the public health implications, clinical management, and experiences and information needs of healthcare providers (HCP) and parents, relating to acute cannabis poising in children. Design/Methods: We searched three databases (Medline, CINAHL, and PsychINFO) from inception until October 2019. Grey literature was searched up to March 2020. We included all records (primary research, knowledge synthesis, editorials, letters/opinion pieces, government websites and news articles) reported in English or French. We defined acute cannabis poisoning as unintended exposure to cannabis or cannabis product(s) that led to the need for acute medical advice or treatment. A primary reviewer screened all identified publications and a secondary reviewer screened excludes. Records were categorized by area (public health implications, clinical management, experiences and information needs) and mapped based on reported outcomes and record type. Results: We identified 4644 records and included 158 (knowledge syntheses [n=3]; primary research [n=95]; editorials, commentaries, and letters [n=18]; education or media for HCP [n=15]; and education or media for the public [n=27]). Public health implications were addressed by 129 (82%), often reporting increasing incidence of acute paediatric cannabis poisonings. 116 records (51 [44%] case studies) reported or discussed clinical characteristics and/or management of acute paediatric cannabis poisoning, including signs and symptoms (92%), use of toxicology screening (60%), type of clinical management (52%) and treatment recommendations (36%). Few sources addressed either HCP (n=5) or parent (n=1) experiences or information needs. Conclusion: The increasing incidence of acute cannabis poisonings and liberalization of cannabis legislation is clear, however, evidence around the clinical management is limited. Rigorous studies of suggested clinical treatments are needed to develop an evidence-base from which data can be synthesized and appraised, in order to drive the development of clinical recommendations. Additionally, further research exploring HCP and parent experiences and information needs around cannabis poisoning is warranted.